2012
DOI: 10.1093/pubmed/fds055
|View full text |Cite
|
Sign up to set email alerts
|

Sexual practices of young educated men: implications for further research and health education in Kingdom of Saudi Arabia (KSA)

Abstract: and recommendations Our study was the first to report the existence of premarital sexual practices among young educated men in KSA. There is a need to identify in detail the risks and the knowledge gaps, and base sexual health awareness among youth on such knowledge in order to prevent the spread of STIs and HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 14 publications
9
27
0
Order By: Relevance
“…The present study indicated the presence of multi-sex partners, alcohol use, and amphetamine consumption among Iranian students is consistent to the studies undertaken in the same context in other Islamic countries (Ajuwon et al, 2005; Kagimu et al, 2012 ; Maswanya et al, 2009 ; Mohammad et al, 2007 ; Mohammadi et al, 2006 ; Raheel et al, 2013 ). Furthermore, self-efficacy was the only predictor of using condoms in high risk sexual relations from among the EPPM theoretical variables and added self-control construct.…”
Section: Discussionsupporting
confidence: 91%
“…The present study indicated the presence of multi-sex partners, alcohol use, and amphetamine consumption among Iranian students is consistent to the studies undertaken in the same context in other Islamic countries (Ajuwon et al, 2005; Kagimu et al, 2012 ; Maswanya et al, 2009 ; Mohammad et al, 2007 ; Mohammadi et al, 2006 ; Raheel et al, 2013 ). Furthermore, self-efficacy was the only predictor of using condoms in high risk sexual relations from among the EPPM theoretical variables and added self-control construct.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence about sexual behavior of Arab young people is scarce [18,141], but premarital sex has been reported by 7% of college students and 4% of youth aged 15e24 years from Jordan [142], 31% of male college students from Saudi Arabia [143], and 1/3 of males and 1/10 of female adolescents from Tunisia [144]. Studies suggest that premarital sex often occurs in the context of secrecy, poor knowledge, lack of access to reproductive health services, and limited communication with parents [18,141,143,145]. A United Nations Children's Fund analysis found that adolescent girls in MENA had the lowest HIV knowledge of any region [92].…”
Section: Changing Life Trajectoriesmentioning
confidence: 99%
“…Premarital sex activity was reported in 31% of the 225 study participants, comprising of young men, in Riyadh city. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Among the educated men in KSA, 51% agreed that the use of condom prevents sexually transmitted infections (STIs). [ 13 17 18 ]…”
Section: Discussionmentioning
confidence: 99%